The intriguing effect of ethanol and nicotine on acetylcholine-sensitive potassium current IKAch: Insight from a quantitative model - Šimurda, Jiří; Šimurdová, Milena; Bébarová, Markéta (PloS one, 2019)
Recent experimental work has revealed unusual features of the effect of certain drugs on cardiac inwardly rectifying potassium currents, including the constitutively active and acetylcholine-induced components of acetylcholine-sensitive current (IKAch). These unusual features have included alternating susceptibility of the current components to activation and inhibition induced by ethanol or nicotine applied at various concentrations, and significant correlation between the drug effect and the current magnitude measured under drug-free conditions. To explain these complex drug effects, we have developed a new type of quantitative model to offer a possible interpretation of the effect of ethanol and nicotine on the IKAch channels. The model is based on a description of IKAch as a sum of particular currents related to the populations of channels formed by identical assemblies of different α-subunits. Assuming two different channel populations in agreement with the two reported functional IKAch-channels (GIRK1/4 and GIRK4), the model was able to simulate all the above-mentioned characteristic features of drug-channel interactions and also the dispersion of the current measured in different cells. The formulation of our model equations allows the model to be incorporated easily into the existing integrative models of electrical activity of cardiac cells involving quantitative description of IKAch. We suppose that the model could also help make sense of certain observations related to the channels that do not show inward rectification. This new ionic channel model, based on a concept we call population type, may allow for the interpretation of complex interactions of drugs with ionic channels of various types, which cannot be done using the ionic channel models available so far.
Keywords: Ethanol; acetylcholin; Computer Simulation; biologické modely; nikotin; časové faktory; Time Factors; gating iontového kanálu; Models, Biological; dovnitř usměrňující draslíkové kanály spřažené s G proteiny; Nicotine; G Protein-Coupled Inwardly-Rectifying Potassium Channels; Acetylcholine; ethanol; počítačová simulace; Ion Channel Gating